A High-Fidelity Energy Efficient Path Planner for Unmanned Airships - Recoskie, Steven; Lanteigne, Eric; Gueaieb, Wail (Université d'Ottawa | University of Ottawa, 2017)
This paper presents a comparative study on the effects of grid resolution, vehicle velocity, and wind vector fields on the trajectory planning of unmanned airships. A wavefront expansion trajectory planner that minimizes a multi-objective cost function consisting of flight time, energy consumption, and collision avoidance while respecting the differential constraints of the vehicle is presented. Trajectories are generated using a variety of test environments and flight conditions to demonstrate that the inclusion of a high terrain map resolution, a temporal vehicle velocity, and a spatial wind vector field yields significant improvements in trajectory feasibility and energy economy when compared to trajectories generated using only two of these three elements.
Keywords: path planning; unmanned airship; wavefront expansion